Zambia : Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews Zambia's Second Poverty Reduction Strategy Paper (PRSP) Implementation Progress Report. The report reviews the status of the Poverty Reducing Programs (PRPs) for July 2003-June 2004. It notes improvement in funding to priority PRPs from K140 billion in January 2002-June 2003 to K430 billion in July 2003-June 2004. The report discusses that major improvements in public finance management were achieved in the first half of the budget year 2004, mainly owing to the introduction of the Medium-Term Expenditure Framework and Activity-Based Budgeting.